Pyrroline-5-Carboxylate Reductase 1 Directs the Cartilage Protective and Regenerative Potential of Murphy Roths Large Mouse Mesenchymal Stem Cells - Tejedor, Gautier; Contreras-Lopez, Rafael; Barthelaix, Audrey; Ruiz, Maxime; Noël, Danièle; De Ceuninck, Frédéric; Pastoureau, Philippe; Luz-Crawford, Patricia; Jorgensen, Christian; Djouad, Farida (Frontiers in Cell and Developmental Biology, 2021)
Murphy Roths Large (MRL) mice possess outstanding capacity to regenerate several tissues. In the present study, we investigated whether this regenerative potential could be associated with the intrinsic particularities possessed by their mesenchymal stromal cells (MSC). We demonstrated that MSC derived from MRL mice (MRL MSC) display a superior chondrogenic potential compared to C57BL/6 MSC (BL6 MSC). This higher chondrogenic potential of MRL MSC was associated to a higher expression level of pyrroline-5-carboxylate reductase 1 (PYCR1), an enzyme that catalyzes the biosynthesis of proline, in MRL MSC compared to BL6 MSC. The knockdown of PYCR1 in MRL MSC, using a specific small interfering RNA (siRNA), abolish their chondrogenic potential. Moreover, we showed that PYCR1 silencing in MRL MSC induced a metabolic switch from glycolysis to oxidative phosphorylation. In two in vitro chondrocyte models that reproduce the main features of OA chondrocytes including a downregulation of chondrocyte markers, a significant decrease of PYCR1 was observed. A downregulation of chondrocyte markers was also observed by silencing PYCR1 in freshly isolated healthy chondrocytes. Regarding MSC chondroprotective properties on chondrocytes with OA features, we showed that MSC silenced for PYCR1 failed to protect chondrocytes from a reduced expression of anabolic markers while MSC overexpressing PYCR1 exhibited an increased chondroprotective potential. Finally, using the ear punch model, we demonstrated that MRL MSC induced a regenerative response in non-regenerating BL6 mice while BL6 and MRL MSC deficient for PYCR1 did not. In conclusion, our results provide evidence that MRL mouse regenerative potential is, in part, attributed to their MSC that exhibit higher PYCR1-dependent glycolytic potential, differentiation capacities, chondroprotective abilities and regenerative potential than BL6 MSC.